Misvaluing Innovation - Cohen, Lauren; Diether, Karl; Malloy, Christopher (Review of Financial Studies, 2013)
AFA Meetings in Chicago for helpful comments and suggestions. We are grateful for funding from the We demonstrate that a firm’s ability to innovate is predictable, persistent, and relatively simple to compute, and yet the stock market ignores the implications of past successes when valuing future innovation. We show that two firms that invest the exact same in research and development (R&D) can have quite divergent, but predictably divergent, future paths. Our approach is based on the simple premise that while future outcomes associated with R&D investment are uncertain, the past track records of firms may give insight into their potential for future success. We show that a long-short portfolio strategy that takes advantage of the information in past track records earns abnormal returns of roughly 11 percent per year. Importantly, these past track records also predict divergent future real outcomes in patents, patent citations, and new product innovations. Firms engage in a variety of activities. Some of these activities are straightforward, and easy to assess how they will impact firm value (e.g., maintenance capital expenditures). However, some of these activities, while crucially important for the discounted value of a